Pengaruh Financial Technology, Social Environment, Financial Literacy dan Lifestyle Terhadap Perilaku Keuangan Mahasiswa Fakultas Ekonomi Universitas Slamet Riyadi Surakarta - Deva Novia Arinta; Naili Amalia (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The purpose of this research was to investigate the influence of financial technology, social environment, financial literacy, and lifestyle on the financial behaviors of students in the Faculty of Economics at Slamet Riyadi University, Surakarta. Utilizing a quantitative research methodology, the study sampled 100 students through a simple random sampling technique. Data were analyzed using descriptive statistics, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results revealed that financial technology (X1) has a positive and statistically significant impact on the financial behaviors of students in the Faculty of Economics. Conversely, the social environment (X2) exhibits a positive but non-significant effect on the financial behaviors of these students. Additionally, financial literacy (X3) was found to have a positive and significant influence on the financial behaviors of the students. Moreover, the findings indicated that lifestyle (X4) also positively and significantly affects the financial behaviors of the students at the Faculty of Economics at Slamet Riyadi University, Surakarta.